Management of Phosphatidylinositol-3-Kinase Inhibitor-Associated Hyperglycemia. (January 2022) - Goncalves, Marcus D.; Farooki, Azeez
Phosphatidylinositol-3-kinase (PI3K) pathway hyperactivation has been associated with the development of cancer and treatment resistance. PI3K inhibitors are now used to treat hormone receptor-positive (HR+), human epidermal growth factor receptor-2–negative (HER2−), PIK3CA- mutated advanced breast cancer. Hyperglycemia, a frequently observed adverse event with PI3K inhibitors (PI3Ki), is regarded as an on-target effect because inhibition of the PI3K pathway has been shown to decrease glucose transport and increase glycogenolysis and gluconeogenesis. PI3Ki-induced hyperglycemia results in a compensatory increase in insulin release, which has been shown to reduce the efficacy of treatment by reactivating the PI3K pathway in preclinical models. Patients with an absolute or relative deficiency in insulin, and those with insulin resistance or pancreatic dysfunction, may experience exacerbated or prolonged hyperglycemia. Therefore, the effective management of PI3Ki-associated hyperglycemia depends on early identification of patients at risk, frequent monitoring to allow prompt recognition of hyperglycemia and its sequelae, and initiating appropriate management strategies. Risk factors for the development of hyperglycemia include older age (≥75 years), overweight/obese at baseline, and family history of diabetes. Consultation with an endocrinologist is recommended for patients considered high risk. The management of PI3Ki-induced hyperglycemia requires an integrative approach that combines diets low in carbohydrates and glucose-lowering medications. Medications that do not affect the PI3K pathway are preferred as the primary and secondary agents for the management of hyperglycemia. These include metformin, sodium-glucose co-transporter 2 inhibitors, thiazolidinediones, and α-glucosidase inhibitors. Insulin should only be considered as a last-line agent for PI3Ki-associated hyperglycemia due to its stimulatory effect of PI3K signaling. Clinical studies show that alpelisib-associated hyperglycemia is reversible and manageable, rarely leading to treatment discontinuation. Management of PI3Ki-associated hyperglycemia in patients with breast cancer should focus on the prevention of acute and subacute complications of hyperglycemia, allowing patients to remain on anticancer treatment longer.